Disaster Education Model for Pre-School Age Children - Khaerudin Khaerudin; Nur Tjahjono Suharto (IAI Ma'arif NUMetro Lampung, 2022)
Disasters are classified into 3 (three) namely natural disasters, non-natural disasters and social disasters. To reduce disaster risk, it is necessary to prioritize a disaster-care attitude with disaster education from an early age in accordance with the habits of a society. This study aims to reveal and analyze the disaster education model in early childhood and at the same time to determine the effectiveness of the learning process. This research is a research library to examine the literature related to research problems by selecting, reading, studying, and reviewing relevant research. Data collection was carried out through literature surveys related to disaster education and studies related to early childhood. Data analysis was performed by editing, classification, and interpretation. Early childhood is a group that is vulnerable to disasters. It is imperative that early childhood get attention to get disaster education as early as possible. Disaster education is very important to be implemented from early age groups to adulthood. BPBD Klaten Regency through Taman Eling, Waspada, and Siaga as a model of disaster education provides disaster learning starting from early childhood Keywords:  Early Childhood, Disaster Mitigation, Disaster Education Model